2022
DOI: 10.1186/s12935-021-02435-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the tumour microenvironment in hepatocellular carcinoma by tyrosine kinase inhibitors: from modulation to combination therapy targeting the microenvironment

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer deaths worldwide. Tyrosine kinase inhibitors (TKIs) remain the backbone of systematic therapy for advanced hepatocellular carcinoma. Sorafenib and lenvatinib are currently approved as first-line therapeutic drugs, and regorafenib and cabozantinib are applied as second-line treatments. With inhibition of angiogenesis as the main target, TKIs exert a profound effect on the tumour microenvironment (TME). The TME is a complex mixture of cellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 167 publications
0
19
0
Order By: Relevance
“…In this study, we reported a case in which conversion therapy for initially unresectable HCC was successfully achieved following the combination treatment of lenvatinib and camrelizumab. After searching the ClinicalTrials.gov database, we found several clinical trials that used lenvatinib and camrelizumab combination for advanced HCC, including NCT04443309, NCT04627012, and NCT04639284 [ 23 , 24 ]. However, it is essential to initiate more clinical trials to evaluate the efficacy, safety, and conversion rate of this novel combination regimen for HCC and to investigate suitable markers to identify the target population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we reported a case in which conversion therapy for initially unresectable HCC was successfully achieved following the combination treatment of lenvatinib and camrelizumab. After searching the ClinicalTrials.gov database, we found several clinical trials that used lenvatinib and camrelizumab combination for advanced HCC, including NCT04443309, NCT04627012, and NCT04639284 [ 23 , 24 ]. However, it is essential to initiate more clinical trials to evaluate the efficacy, safety, and conversion rate of this novel combination regimen for HCC and to investigate suitable markers to identify the target population.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is recommended as a first-line oral systemic therapy for HCC which has been reported to have immune-modulatory effects (32)(33)(34). It can modulate the cytokine phenotype of macrophage toward a profile that promotes the function of immune effector cells.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…TKIs can also activate immune cells, and there is no significant overlap in the toxicity of TKIs and ICIs. 233 A phase III clinical trial showed that axitinib combined with pembrolizumab significantly prolonged the survival of RCC patients, compared with sunitinib alone. 234 Clinical trials of lenvatinib combined with pembrolizumab for endometrial cancer, HCC, and RCC have also shown encouraging safety and efficacy.…”
Section: Mechanisms Of Tki Resistancementioning
confidence: 99%